Serum changes in sTWEAK and its scavenger receptor sCD163 in ultramarathon athletes running the 24-h race. (January 2021) - Benedetti, Serena; Gemma Nasoni, Maria; Palma, Francesco; Citarella, Roberto; Luchetti, Francesca
Graphical abstract: Highlights: The 24-h ultramarathon is associated with acute tissue injury and inflammation. sTWEAK, sCD163, and IL-6 serum levels were monitored before and after the race. Reduced sTWEAK and increased sCD163 and IL-6 levels were observed at post-race. Correlations were found between IL-6, sCD163, sTWEAK and cardiac damage markers. Abstract: In the present investigation, the serum changes of sTWEAK levels, a multifunctional cytokine involved in tissue response to acute injury and inflammation, and of its scavenger receptor sCD163, were monitored for the first time in ultramarathon athletes running the 24-h competition, an extremely demanding race in terms of muscular and physiological exertion. To this aim, venous blood samples were collected from each participant (n = 22, M = 12, F = 10) both before and immediately after the 24-h running. Other than sTWEAK and sCD163, the common serum biomarkers of inflammation (namely CRP and IL-6) and tissue injury (such as CPK, LDH, CPK-MB, troponin-I, and NT-proBNP) were evaluated. All parameters were within the reference ranges at baseline, indicating no alterations of the normal physiological processes before the competition; on the contrary, most biomarkers of tissue damage and inflammation strongly increased after the ultramarathon race. Interestingly, a significant decrement of sTWEAK levels associated with an increment of its scavenger receptor sCD163 was observed at post-race. Positive relationships were evidenced between IL-6 and sCD163 levels and the markers of cardiac damage troponin-I and NT-proBNP. On the contrary, sTWEAK showed an inverse correlation with IL-6 and NT-proBNP. This study opens the way to further investigations aimed at clarifying the role of TWEAK pathway during the prolonged ultraendurance activity, paying particular attention to the link of IL-6, CD163 and TWEAK with the cardiac function.